Control of hybrid power system based renewable energy generations using PID controller - Mohamed Regad; M'hamed Helaimi; Rachid Taleb; Ahmed M. Othman; Hossam A. Gabbar (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
This paper addresses to integrate an optimal Proportional-Integrator-Derivative controller for frequency regulation in an isolated microgrid power system based renewable generation. This autonomous microgrid system is composed of Distributed Energy Sources like wind, solar, Diesel Engine Generator, Fuel Cells system, and two different storage devices such as Battery Energy Storage System and Flywheel Energy Storage System. Optimal tuning of the investigated controller is considered as the main problem to be resolved using the Krill Herd algorithm through an objective function. The obtained results are also accomplished with and without the battery energy storage system. The comparison of system performance shows that the proposed control scheme based Krill Herd Algorithm is better than the Genetic Algorithm in the improvement of system performance.